Nutritional assessment of hospitalized HIV-infected patients by the phase angle z-score measurement - Araujo Antunes, A. [UNESP]; Alves Pereira Rodrigues, A. P. [UNESP]; Geraix, J. [UNESP]; Vaz de Arruda Silveira, L. [UNESP]; Camara Marques Pereira, P. [UNESP]; Barros Leite Carvalhaes, Ma A. [UNESP] (Aula Médica Ediciones, 2012)
Background: This study analyzed the phase-angle (PA) values of hospitalized HVI-infected patients by comparing them with those reported for a healthy population and investigated their relation with nutritional parameters.Methods: This is a cross-sectional study including 101 hospitalized patients diagnosed with HIV infection and evaluated by bioimpedance, anthropometry and biochemical tests. The phase angle values, weight loss percentage (%WL), body mass index (BMI), arm muscle circumference (AMC), tricipital skinfold (TSF), body fat percentage (%BF) and albumin were considered. In order to compare with values for the healthy population, the PA z-score of the patients under study was calculated. Spearman's correlation and the multiple linear regression model were used to identify nutritional parameters associated with the PA z-score.Results: The patients showed a mean PA z-score of -2.6 +/- 1.5, and only 6.6% of them with a positive value. The PA z-score values correlated with %WL (r = -0.51; p < 0.0001), albumin (r = 0.49; p < 0.0001), BMI (r = 0.58; p < 0.0001), AMC (r = 0.41; p < 0.0001), TSF (r = 0.47; p < 0.001) and %BF (r = 0.48, p < 0.0001). In multiple analysis %WL (p = 0.008), albumin (p = 0.01), AMC (p < 0.0001) and %BF (p = 0.0003) remained associated with the score.Conclusions: Low PA z-score values were observed, suggesting a worse clinical prognosis for the patients. The inclusion of the PA z-score as a nutritional indicator during care provision to HIV-infected patients is recommended. (Nutr Hosp. 2012;27:771-774) DOI:10.3305/nh.2012.27.3.5684
Keywords: Electrical bioimpedance; HIV; Nutritional status; Phase angle